Length-weight relationship and morphological studies in the Kashgarian loach Triplophysa yarkandensis (Day, 1877) from the Tarim River, Tarim River Basin, North-West China - Nie, Zhulan; Wu, Hao; Wei, Jie; Zhang, Xue; Ma, Zhenhua (Indian Journal of Fisheries, 2013)
The Kashgarian loach Triplophysa yarkandensis is one of the rare freshwater species distributed in the Tarim River basin of Xinjiang Uygur Autonomous Region in north-west China. Biological information on this species is scarce. As a species caught in the traditional fisheries, the natural resources are nearly exhausted. Attempt to breed this species in captivity has not yet succeeded. The present study was undertaken to investigate selected biological aspects of the species. Truss morphometric measurements were used to assess the principal shape components of different sized T. yarkandensis. A total of 102 numbers of T. yarkandensis were collected from Alaer reach of Tarim River, Tarim River Basin. Wet weight (Wt) and body length (BL) were measured in the laboratory and the length-weight relationship was expressed as Wt = 0.0594Ã—BL2.1669. Our study provides first biological reference to this species in Alaer Reach of Tarim River and the results will provide fundamental information for resource assessment as well as for taking up further aquaculture practices of this species.